Population structure and genetic stock identification in southeastern United States loggerhead sea turtles (Caretta caretta) using genome-wide SNPs - Ian Silver-Gorges; Lisa M. Komoroske; Jamie Adkins; John D. Swenson; David S. Addison; Derek A. Burkholder; Dean A. Bagley; Glenn D. Goodwin; Kristen M. Hart; Joseph B. Pfaller; Brian M. Shamblin; Mariana M. P. B. Fuentes (Conservation Genetics, 2026)
Characterizing the genetic structure and connectivity between populations of endangered species can be used to inform management actions. In vagile species with high gene flow or recently established populations, such characterizations can be difficult to undertake using traditional genetic markers, and genetic stock identification (GSI) may be confounded by allele-sharing between populations. Loggerhead sea turtles ( Caretta caretta ) in the southeastern United States comprise seven management units (MUs) based on female philopatry inferred via mitochondrial DNA sequences, yet nuclear microsatellite data do not reflect divergence. Further, loci for accurate GSI are not currently known. To address this, we generated genome-wide single nucleotide polymorphism (SNP) data from 146 females nesting at individual sites representative of each southeastern United States MU. We found weak (F ST =0.001–0.003) but significant divergence among all MUs, with more notable divergence between the Gulf Coast and Atlantic Ocean MUs, and amongst the Atlantic Ocean MUs. We then used an iterative leave-one-out approach to identify candidate loci for GSI. This approach identified loci that could assign individuals to natal ocean basins (i.e., to the Gulf Coast or to the Atlantic Ocean), and to individual MUs within the Atlantic Ocean, with high (≥90%) success and accuracy. Analyses of genome-wide SNPs refined our understanding of the magnitude and scale of population connectivity in loggerhead turtles in the southeastern United States, and provided a foundation for the development of SNP panels for accurate, fine-scale GSI in sea turtles.

Analysis of measurements from an array of radioxenon samplers near to Hartlepool Nuclear Power Station - M.A. Goodwin; D.L. Chester; S.J. Leadbetter; A. Petts; C. Toth; R. Sarathi; B. Milbrath; M. Mayer; J. Friese; T.W. Bowyer; S. Liljegren; A. Ringbom; et al. (Journal of Environmental Radioactivity, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Characterising the Radionuclide Fingerprint of an Advanced Gas-Cooled Nuclear Power Reactor - M. A. Goodwin; A. Petts; B. D. Milbrath; A. Ringbom; D. L. Chester; T. W. Bowyer; J. L. Burnett; J. Friese; L. Lidey; J. C. Hayes; P. W. Eslinger; M. Mayer; et al. (Pure and Applied Geophysics, 2025)
Radionuclides are monitored in the atmosphere for the signatures of nuclear explosions, as part of the verification of the Comprehensive Nuclear-Test-Ban Treaty (CTBT). Civil nuclear facilities, such as Nuclear Power Plants (NPPs) and Isotope Production Facilities (IPFs) are sources of anthropogenic radionuclides in the atmosphere and these signatures are sometimes indistinguishable to those of a nuclear explosion. In order to improve the understanding of civil radionuclide-emitting facilities and their impact on the International Monitoring System (IMS) of the CTBT, a group of scientists from the UK, US and Sweden are collaborating with EDF Energy UK to measure radionuclide emissions from an Advanced Gas-cooled Reactor (AGR) nuclear power station. Emissions are being measured at the source, via a stack monitor and high-resolution gamma spectrometry measurements of filters and also at tens of kilometres away via three sensitive radioxenon atmospheric samplers. The timing, isotopic composition, activity magnitudes and other release parameters of interest are investigated, to improve the discrimination between a civil radionuclide release and an explosive nuclear test. This paper outlines the work of the Xenon and Environmental Nuclide Analysis at Hartlepool (XENAH) collaboration, describes the equipment fielded and provides initial results from each measurement campaign.

Policy, management, and the ‘Level of Fouling’ scale to transform marine invasion risk reduction from recreational boats - M. Gammon; O. Floerl; S. Happy; K. Leonard; H. Lass; K. Walls; L. Floerl; P. Casanovas; E. Goodwin; S. Hucker; I. Davidson (Journal of Environmental Management, 2025)

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

Advancements in Riverine Fish Movement Modeling: Bridging Environmental Complexity and Fish Behavior - D. P. Zielinski; J. Kerr; K. M. Bærum; O. M. Simmons; A. T. Silva; R. A. Goodwin (Reviews in Fisheries Science & Aquaculture, 2025)

Determination of the source location of anthropogenic radionuclides collected in Finland and Sweden in June 2020 using a multi-technology analysis - Ian Hoffman; P. Mekarski; A. Botti; J. Yi; A. Malo; C. Cochrane; V. Khotylev; J. Kastlander; A. Axelsson; A. Ringbom; M. Moring; T. Karhunen; et al. (Journal of Environmental Radioactivity, 2024)

Risks associated with global warming of 1.5 to 4 °C above pre-industrial levels in human and natural systems in six countries - R. Warren; J. Price; N. Forstenhäusler; O. Andrews; S. Brown; K. Ebi; D. Gernaat; P. Goodwin; D. Guan; Y. He; D. Manful; Z. Yin; et al. (Climatic Change, 2024)
The Topical Collection “Accrual of Climate Change Risk in Six Vulnerable Countries” provides a harmonised assessment of risks to human and natural systems due to global warming of 1.5–4 °C in six countries (China, Brazil, Egypt, Ethiopia, Ghana, and India) using a consistent set of climate change and socioeconomic scenarios. It compares risks in 2100 if warming has reached 3 °C, broadly corresponding to current global greenhouse gas emission reduction policies, including countries’ National Determined Contributions, rather than the Paris Agreement goal of limiting warming to ‘well below’ 2 °C and ‘pursuing efforts’ to limit to 1.5 °C. Global population is assumed either constant at year 2000 levels or to increase to 9.2 billion by 2100. In either case, greater warming is projected to lead, in all six countries, to greater exposure of land and people to drought and fluvial flood hazard, greater declines in biodiversity, and greater reductions in the yield of maize and wheat. Limiting global warming to 1.5 °C, compared with ~ 3 °C, is projected to deliver large benefits for all six countries, including reduced economic damages due to fluvial flooding. The greatest projected benefits are the avoidance of a large increase in exposure of agricultural land to severe drought, which is 61%, 43%, 18%, and 21% lower in Ethiopia, China, Ghana, and India at 1.5 °C than at 3 °C, whilst avoided increases in human exposure to severe drought are 20–80% lower at 1.5 °C than 3 °C across the six countries. Climate refugia for plants are largely preserved at 1.5 °C warming in Ghana, China, and Ethiopia, but refugia shrink in areal extent by a factor of 2, 3, 3, 4, and 10 in Ghana, China, India, Ethiopia, and Brazil, respectively, if warming reaches 3 °C. Economic damages associated with sea-level rise are projected to increase in coastal nations, but more slowly if warming were limited to 1.5 °C. Actual benefits on the ground will also depend on national and local contexts and the extent of future investment in adaptation.

Characteristics of peak exposure to black carbon pollution in school, commute and home environments among school children in an urban community - Kyung Hwa Jung; Kathleen E. Goodwin; James M. Ross; Jing Cai; Steven N. Chillrud; Matthew Perzanowski; Frederica P. Perera; Rachel L. Miller; Stephanie Lovinsky-Desir (Environmental Pollution, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying risks avoided by limiting global warming to 1.5 or 2 °C above pre-industrial levels - Rachel Warren; Oliver Andrews; Sally Brown; Felipe J. Colón-González; Nicole Forstenhäusler; David E. H. J. Gernaat; P. Goodwin; Ian Harris; Yi He; Chris Hope; Desmond Manful; Timothy J. Osborn; et al. (Climatic Change, 2022)
The Paris Agreement aims to constrain global warming to ‘well below 2 °C’ and to ‘pursue efforts’ to limit it to 1.5 °C above pre-industrial levels. We quantify global and regional risk-related metrics associated with these levels of warming that capture climate change–related changes in exposure to water scarcity and heat stress, vector-borne disease, coastal and fluvial flooding and projected impacts on agriculture and the economy, allowing for uncertainties in regional climate projection. Risk-related metrics associated with 2 °C warming, depending on sector, are reduced by 10–44% globally if warming is further reduced to 1.5 °C. Comparing with a baseline in which warming of 3.66 °C occurs by 2100, constraining warming to 1.5 °C reduces these risk indicators globally by 32–85%, and constraining warming to 2 °C reduces them by 26–74%. In percentage terms, avoided risk is highest for fluvial flooding, drought, and heat stress, but in absolute terms risk reduction is greatest for drought. Although water stress decreases in some regions, it is often accompanied by additional exposure to flooding. The magnitude of the percentage of damage avoided is similar to that calculated for avoided global economic risk associated with these same climate change scenarios. We also identify West Africa, India and North America as hotspots of climate change risk in the future.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Changing climate reallocates the carbon debt of frequent‐fire forests - Marissa J. Goodwin; Malcolm P. North; Harold S. J. Zald; Matthew D. Hurteau (Global Change Biology, 2020)
Ongoing climate change will alter the carbon carrying capacity of forests as they adjust to climatic extremes and changing disturbance regimes. In frequent‐fire forests, increasing drought frequency and severity are already causing widespread tree mortality events, which can exacerbate the carbon debt that has developed as a result of fire exclusion. Forest management techniques that reduce tree density and surface fuels decrease the risk of high‐severity wildfire and may also limit drought‐induced mortality by reducing competition. We used a long‐term thinning and burning experiment in a mixed‐conifer forest to investigate the effects of the 2012–2015 California drought on forest carbon dynamics in each treatment, including the carbon emissions from a second‐entry prescribed fire that followed the drought. We assessed differences in carbon stability and tree survival across treatments, expecting that both carbon stability and survival probability would increase with increasing treatment intensity (decreasing basal area). Additionally, we analyzed the effects of drought‐ mortality on second‐entry burn emissions and compared emissions for the first‐ and second‐entry burns. We found a non‐linear relationship between treatment intensity and carbon stability, which was in part driven by varying relationships between individual tree growing space and survival across treatments. Drought mortality increased dead tree and surface fuel carbon in all treatments, which contributed to higher second‐entry burn emissions for two of the three burn treatments when compared to the first burn. Our findings suggest that restoration treatments will not serve as a panacea for ongoing climate change and that the carbon debt of these forests will become increasingly unstable as the carbon carrying capacity adjusts to severe drought events. Managing the carbon debt with prescribed fire will help reduce the risk of additional mortality from wildfire, but at an increasing carbon cost for forest management.

Human Tat-specific factor 1 binds the HIV-1 genome and selectively transports HIV-1 RNAs - Molly J. Hulver; Julia P. Trautman; Amanda P. Goodwin; Sebastian K. Roszczenko; Keir H. Fogarty; Heather B. Miller (Molecular Biology Reports, 2020)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

In situ Autonomous Acquisition and Preservation of Marine Environmental DNA Using an Autonomous Underwater Vehicle - Kevan M. Yamahara; Christina M. Preston; James Birch; Kristine Walz; Roman Marin; Scott Jensen; Douglas Pargett; Brent Roman; William Ussler; Yanwu Zhang; John Ryan; Brett Hobson; et al. (Frontiers in Marine Science, 2019)

Aquatic habitat response to climate-driven hydrologic regimes and water operations in a montane reservoir in the Pacific Northwest, USA - D. E. Weigel; L. C. Vilhena; P. Woods; D. Tonina; A. Tranmer; R. Benjankar; C. L. Marti; P. Goodwin (Aquatic Sciences, 2017)

Adapting astronomical source detection software to help detect animals in thermal images obtained by unmanned aerial systems - S. N. Longmore; R. P. Collins; S. Pfeifer; S. E. Fox; M. Mulero-Pázmány; F. Bezombes; A. Goodwin; M. De Juan Ovelar; J. H. Knapen; S. A. Wich (International Journal of Remote Sensing, 2017)

A crop and cultivar-specific approach to assess future winter chill risk for fruit and nut trees - R. Darbyshire; P. Measham; I. Goodwin (Climatic Change, 2016)

Potential for Southern Hemisphere climate surprises - P. A. MAYEWSKI; T. BRACEGIRDLE; I. GOODWIN; D. SCHNEIDER; N. A. N. BERTLER; S. BIRKEL; A. CARLETON; M. H. ENGLAND; J‐H. KANG; A. KHAN; J. RUSSELL; J. TURNER; et al. (Journal of Quaternary Science, 2015)
Climate model results suggest that future climate change in Antarctica will be accompanied by continued strengthening and poleward contraction of the Southern Ocean westerly wind belt. Paleoclimate records suggest past changes in the westerly winds can be abrupt and that healing of the Antarctic ozone hole could lead to poleward contraction of the westerlies and increased meridional atmospheric transport of warm air regionally into Antarctica. An abrupt shift to more meridional circulation could lead to notable changes in moisture availability for extra‐Antarctic regions, increased Antarctic ice sheet disintegration and more rapid sea‐level rise.

Asymmetric Cell–Matrix and Biomechanical Abnormalities in Elastin Insufficiency Induced Aortopathy - Varun K. Krishnamurthy; Ashlie N. Evans; Janaka P. Wansapura; Hanna Osinska; Kelsey E. Maddy; Stefanie V. Biechler; Daria A. Narmoneva; Richard L. Goodwin; Robert B. Hinton (Annals of Biomedical Engineering, 2014)

A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Ian D. Goodwin; Stuart Browning; Andrew M. Lorrey; Paul A. Mayewski; Steven J. Phipps; Nancy A. N. Bertler; Ross P. Edwards; Tim J. Cohen; Tas van Ommen; Mark Curran; Cameron Barr; J. Curt Stager (Climate Dynamics, 2014)

Numerical modelling of plasticity induced by transcranial magnetic stimulation - M. T. Wilson; D. P. Goodwin; P. W. Brownjohn; J. Shemmell; J. N. J. Reynolds (Journal of Computational Neuroscience, 2014)

Crustal architecture of the Capricorn Orogen, Western Australia and associated metallogeny - S. P. Johnson; A. M. Thorne; I. M. Tyler; R. J. Korsch; B. L. N. Kennett; H. N. Cutten; J. Goodwin; O. Blay; R. S. Blewett; A. Joly; M. C. Dentith; A. R. A. Aitken; et al. (Australian Journal of Earth Sciences, 2013)

Genotypic variability and aggressiveness of Bipolaris oryzae in the Philippines - M. R. G. Burgos; M. L. B. Katimbang; M. A. G. Dela Paz; G. A. Beligan; P. H. Goodwin; I. P. Ona; R. P. Mauleon; E. Y. Ardales; C. M. Vera Cruz (European Journal of Plant Pathology, 2013)

Chlorophyll fluorescence for quantification of fungal foliar infection and assessment of the effectiveness of an induced systemic resistance activator - J. Tung; P. H. Goodwin; T. Hsiang (European Journal of Plant Pathology, 2013)

West Antarctica's sensitivity to natural and human‐forced climate change over the Holocene - P. A. Mayewski; K. A. Maasch; D. Dixon; S. B. Sneed; R. Oglesby; E. Korotkikh; M. Potocki; B. Grigholm; K. Kreutz; A. V. Kurbatov; N. Spaulding; J. C. Stager; et al. (Journal of Quaternary Science, 2013)
The location and intensity of the austral westerlies strongly influence southern hemisphere precipitation and heat transport with consequences for human society and ecosystems. With future warming, global climate models project increased aridity in southern mid‐latitudes related to continued poleward contraction of the austral westerlies. We utilize Antarctic ice cores to investigate past and to set the stage for the prediction of future behaviour of the westerlies. We show that Holocene West Antarctic ice core reconstructions of atmospheric circulation sensitively record naturally forced progressive as well as abrupt changes. We also show that recent poleward migration of the westerlies coincident with increased emission of greenhouse gases and the Antarctic ozone hole has led to unprecedented penetration, compared with >100,000 years ago, of air masses bringing warmth, extra‐Antarctic source dust and anthropogenic pollutants into West Antarctica. Copyright © 2012 John Wiley & Sons, Ltd.

Serum insulin-like growth factors and mortality in localised and advanced clinically detected prostate cancer - Mari-Anne Rowlands; Jeff M. P. Holly; Freddie Hamdy; Joshua Phillips; Louise Goodwin; Gemma Marsden; David Gunnell; Jenny Donovan; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2012)

A comparison of two class 10 pathogenesis-related genes from alfalfa and their activation by multiple stresses and stress-related signaling molecules - B. Bahramnejad; P. H. Goodwin; J. Zhang; C. Atnaseo; Larry R. Erickson (Plant Cell Reports, 2010)

Differential expression of eight defensin genes of N. benthamiana following biotic stress, wounding, ethylene, and benzothiadiazole treatments - Bahman Bahramnejad; L. R. Erickson; C. Atnaseo; P. H. Goodwin (Plant Cell Reports, 2009)

Behavioral effects and pharmacokinetics of gamma-hydroxybutyrate (GHB) precursors gamma-butyrolactone (GBL) and 1,4-butanediol (1,4-BD) in baboons - A. K. Goodwin; P. R. Brown; E. E. W. Jansen; C. Jakobs; K. M. Gibson; E. M. Weerts (Psychopharmacology, 2009)

Differential expression of eight defensin genes of N. benthamiana following biotic stress, wounding, ethylene, and benzothiadiazole treatments - Bahman Bahramnejad; L. R. Erickson; A. Chuthamat; P. H. Goodwin (Plant Cell Reports, 2009)

Expression of a metacaspase gene of Nicotiana benthamiana after inoculation with Colletotrichum destructivum or Pseudomonas syringae pv. tomato, and the effect of silencing the gene on the host response - L. Hao; P. H. Goodwin; T. Hsiang (Plant Cell Reports, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Chronic intragastric administration of gamma-butyrolactone produces physical dependence in baboons - Amy K. Goodwin; Roland R. Griffiths; P. Rand Brown; Wolfgang Froestl; Cornelis Jakobs; K. Michael Gibson; Elise M. Weerts (Psychopharmacology, 2006)

Silencing an ACC oxidase gene affects the susceptible host response of Nicotiana benthamiana to infection by Colletotrichum orbiculare - X. C. Shan; P. H. Goodwin (Plant Cell Reports, 2006)

The effects of a branched chain amino acid mixture supplemented with tryptophan on biochemical indices of neurotransmitter function and decision-making - A. Scarnà; S. F. B. McTavish; P. J. Cowen; G. M. Goodwin; R. D. Rogers (Psychopharmacology, 2005)

Spontaneous and precipitated withdrawal after chronic intragastric administration of gamma-hydroxybutyrate (GHB) in baboons - Elise M. Weerts; Amy K. Goodwin; Roland R. Griffiths; P. Rand Brown; Wolfgang Froestl; Cornelis Jakobs; K. Michael Gibson (Psychopharmacology, 2005)

Y chromosome haplogroups of elite Ethiopian endurance runners - Colin N. Moran; Robert A. Scott; Susan M. Adams; Samantha J. Warrington; Mark A. Jobling; Richard H. Wilson; William H. Goodwin; Evelina Georgiades; Bezabhe Wolde; Yannis P. Pitsiladis (Human Genetics, 2004)

Mid latitude winter climate variability in the South Indian and southwest Pacific regions since 1300 AD - I. D. Goodwin; T. D. van Ommen; M. A. J. Curran; P. A. Mayewski (Climate Dynamics, 2004)

Comparison of relative RT-PCR and northern blot analyses to measure expression of β-1,3-glucanase inNicotiana benthamiana infected withColltotrichum destructivum - J. D. Dean; P. H. Goodwin; T. Hsiang (Plant Molecular Biology Reporter, 2002)

Assessment of the Ready Biodegradability of Bisphenol A - R. J. West; P. A. Goodwin; G. M. Klecka (Bulletin of Environmental Contamination and Toxicology, 2001)

Resistance to Botrytis cinerea in scented geranium transformed with a gene encoding the antimicrobial protein Ace -AMP1 - Y.-M. Bi; B. P. A. Cammue; P. H. Goodwin; S. KrishnaRaj; P. K. Saxena (Plant Cell Reports, 1999)

Mutations that modify or exclude binding of the QA ubiquinone and carotenoid in the reaction center from Rhodobacter sphaeroides - Justin P. Ridge; Marion E. van Brederode; Matthew G. Goodwin; Rienk van Grondelle; Michael R. Jones (Photosynthesis Research, 1999)

Executive function and uptake of 99m Tcexametazime shown by single photon emission tomography after oral idazoxan in probable Alzheimer-type dementia - Guy M. Goodwin; Stuart C. Conway; Helene Peyro-Saint-Paul; Mike F. Glabus; Ronan E. O'Carroll; Klaus P. Ebmeier (Psychopharmacology, 1997)

Changes in gravity inhibit lymphocyte locomotion through type I collagen - Neal R. Pellis; Thomas J. Goodwin; Diana Risin; Bradley W. McIntyre; Roland P. Pizzini; David Cooper; Tacey L. Baker; Glenn F. Spaulding (In Vitro Cellular & Developmental Biology - Animal, 1997)

Geobacter metallireducens gen. nov. sp. nov., a microorganism capable of coupling the complete oxidation of organic compounds to the reduction of iron and other metals - D. R. Lovley; S. J. Giovannoni; D. C. White; J. E. Champine; E. J. P. Phillips; Y. A. Gorby; S. Goodwin (Archives of Microbiology, 1993)

Dithiothreitol liberates non-acid labile sulfide from brain tissue of H2S-poisoned animals - Marcus W. Warenycia; Lome R. Goodwin; Donna M. Francom; Fred P. Dieken; Sam B. Kombian; R. J. Reiffenstein (Archives of Toxicology, 1990)

Mapping of some genes involved in C-1 metabolism in the facultative methylotroph Methylobacterium sp strain AM1 (Pseudomonas AM1) - P. K. Tatra; P. M. Goodwin (Archives of Microbiology, 1985)